SCIENCE LITERACY: THE DEVELOPMENT OF THE CONCEPT OF SKELETONS IN BRAZILIAN STUDENTS. - Bartoszeck, Amauri Betini; Bartoszeck, Alexandra Consuelo de P. S.; Tunnicliffe, Sue Dale (EDUCERE - Revista da Educação da UNIPAR, 2008)
This study is concerned with the development of the conceptions of vertebrate skeletons held by students. It is based on a quantitative investigation involving a total of 1890 students in Southern Brazil between ages of 4, or 6, to 25. This a cross-sectional study that investigates the structuring of understanding of bones and skeletons by means of the drawings of the students who were presented with taxidermy specimens of a rat, a woodpecker, a fish and asked to draw what they thought was inside these animals, including themselves. The resultant 8145 drawings were analyzed following a scoring protocol and then subjected to a multivariate linear statistical model to evaluate the significance of age, gender and animal being drawn. Gender differences were not significant. The majority of the students failed to understand the skeleton as a functional integrated unit. Implications for science literacy and biological education are discussed.